Association of asthma and sleep insufficiency among South Korean adolescents: analysis of web-based self-reported data from the Korean youth risk behavior web-based survey. (3rd March 2020) - Han, Chang Hoon; Chung, Jae Ho
Abstract: Objectives : Weekend oversleep or catch-up sleep is common among adolescents, but relatively few data are available with regard to its effects on asthma. Our aim was to investigate whether weekend oversleep is associated with ever having asthma among Korean adolescents. Methods : We analyzed web-based self-reported data from the Korean Youth Risk Behavior Web-based Survey in 25, 927 physician-diagnosed adolescent asthma cases and 266, 160 non-asthma cases. Self-report questionnaires were used to assess socioeconomic status, health behaviors, psychological factors and sleep patterns. Multiple logistic regression after adjusting for factors was used to determine the association between sleep and asthma. Results : The asthma group slept less (≤5 hours: 23.9% vs. 22.8%) had a later weekend bedtime (≥1:00 AM: 58.1% vs. 57.8%), and an earlier weekend wake time (≤7:00 AM: 18.1% vs. 17.0%) compared to the non-asthma group. After multiple logistic regression, a sleep duration ≤5 hours (odds ratio (OR), 1.09; 95% confidence interval (CI), 1.04–1.14) and weekend "early bird" (weekend wake time ≤7:00 AM: OR, 1.03; 95% CI, 1.00–1.07) were significantly associated with an increased frequency of asthma. Long weekend catch-up sleep (weekend sleep duration minus weekday sleep duration ≥2 hours) was significantly associated with a decreased frequency of asthma (OR, 0.98; 95% CI, 0.94–0.99). Conclusion : Long weekend catch-up sleep, as an indicator of insufficient weekday sleep, is associated with a decreased frequency of asthma in Korean adolescents.